Design and implementation of flywheel energy storage system for supporting critical load - Viknesh, Punichelvan (2013)
Flywheel energy storage system (FESS) is a system that can store energy in mechanical forth and release out in electrical form. Nowadays, energy storage systems were widely used such as battery, hydroelectric, fossil fuels and also flywheel energy storage. The main principle of flywheel is the more energy that enters the systems the faster it rotates. The aim of this study is to design and implement a FESS for critical load. Then, period of power generated by FESS was analyzed. Besides that, the voltage that generated by FESS was compared based on minimum value of capacitance used in self excited generator (SEIG). Firstly, a thin firm shaped flywheel rotor was fabricated and it was assembled to the SEIG. FESS consists of a self-excited capacitance induction motor-generator set, power exchange circuit and flywheel rotor. When, there is an ac source, the flywheel rotor start to rotate and it stores energy. Then, the stored energy can be released to the critical load when blackout occurs. The energy stored in the system depends on the properties and moment of inertia of flywheel rotor. The obtained result indicated 47pF is the suitable minimum value of the capacitance of SEIG, and it followed by 33j.tF and 68jtF. The result shows FESS potential to store energy for short period. This study can be a significant initiation to an energy storage system.